1997
DOI: 10.1161/01.hyp.29.1.286
|View full text |Cite
|
Sign up to set email alerts
|

Converting Enzyme Inhibitor Improves Forearm Reactive Hyperemia in Essential Hypertension

Abstract: Endothehal function 1s known to be ImpaIred m essential hypertensive patients In this study, we examined whether antihypertensive drugs improve forearm vasochlatory response to reactive hyperenna m 26 patients with essential hypertension (6222 years) without dtabetes melhtus, hyperhpldemla, coronary heart disease, or cerebrovascular disease AntIhypertensive drugs were never given or were chscontmued for at least 4 weeks before the study Patients were treated with monotherapy of &her temocaprtl (2 or 4 mg, n= 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
4
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 42 publications
8
69
4
1
Order By: Relevance
“…But several other studies have demonstrated that treatment with a calcium antagonist did not improve forearm vasodilator response to reactive hyperemia or to acetylcholine (9,10,22). In our findings, prolonged (8 weeks of oral treatment) amlodipine administration did improve endothelium-dependent vasodilation in essential hypertensive patients.…”
Section: Fig 3 the Vasodilatory Response To Acetylcholine Was Signicontrasting
confidence: 69%
See 2 more Smart Citations
“…But several other studies have demonstrated that treatment with a calcium antagonist did not improve forearm vasodilator response to reactive hyperemia or to acetylcholine (9,10,22). In our findings, prolonged (8 weeks of oral treatment) amlodipine administration did improve endothelium-dependent vasodilation in essential hypertensive patients.…”
Section: Fig 3 the Vasodilatory Response To Acetylcholine Was Signicontrasting
confidence: 69%
“…Because we did not assess FBF responses to sodium nitroprusside infusion after antihypertensive treatment, it may appear that this finding is inconclusive. However, Taddei et al found that the response to sodium nitroprusside was not changed after antihypertensive treatment (19), and other studies have also reported that endothelium-independent vasodilation did not change after treatment (9,10,12,22). We therefore consider that our findings on endothelium-dependent vasodilation could be conclusive.…”
Section: Fig 3 the Vasodilatory Response To Acetylcholine Was Signisupporting
confidence: 46%
See 1 more Smart Citation
“…26 The contribution of increase in local HGF expression by ACE inhibition to endothelial function may also be more general, given that treatment with ACE inhibitors is well known to improve endothelial dysfunction in human hypertensive patients. 27,28 However, the present study has limitations. Recent studies demonstrated the lack of chymase, an alternative Ang II-generating enzyme, in a porcine model.…”
Section: Discussionmentioning
confidence: 81%
“…The procedure has been previously published in detail. 17 Reactive hyperaemia ratio was calculated as hyperaemia/baseline value of FBF, reflecting endothelium-dependent vasodilatation. The nitroglycerin-induced hyperaemia/baseline value of FBF was calculated as endothelium-independent vasodilatation.…”
Section: Measurement Of Fbfmentioning
confidence: 99%